Analysis of heavy metal content of cadmium (Cd) in milkfish (Chanos chanos Forsk) from milkfish farms in Bima Bay - Bukhari Muslim; Khairuddin Khairuddin; M. Yamin; Kusmiyati Kusmiyati (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram, 2022)
The research aims to analysis of the content of heavy metals cadmium (Cd) in milkfish (Chanos chanos Forsk) from the encroachment of Bima bay at year 2020. The benefit of this study is to provide information related to the content of heavy metals cadmium (Cd) in milkfish (Chanos chanos Forsk) and protect the community or consumers from heavy metal contaminants. The research was conducted in Bima Bay, namely in 2 research locations, namely Malay village, Bima City, and Palibelo, Bima Regency. This type of research is descriptive explorative researchÃ¢â¬âsampling techniques using purposive sampling. Samples of milkfish were taken directly on the pond area of 3 heads in each location. Then the sample is put in the sample box that has previously been washed clean. The research samples were then analyzed of the content of heavy metal cadmium (Cd) using Atomic Absorption Spectrophotometer tool. The results showed that at the palibelo research site, Bima Regency in PB 1 samples contains cadmium (Cd) of 30 ppm, PB 2 samples of 40 ppm, and PB 3 samples of 10 ppm. Furthermore, at the location of Malay village, Bima City on KM 1 sample of 30 ppm, on KM 2 sample of 40 ppm, and KM 3 sample of 20 ppm. The content of heavy metal cadmium (Cd) in milkfish (Chanos chanos forsk) from Bima Bay exceeds the threshold by BPOM Regulation No. 5 of 2018 is 0.1 ppm. The presence of heavy metal content cadmium (Cd) that exceeds this threshold indicates that the waters of Bima Bay have been contaminated by heavy metals Cadmium (Cd).